2011
DOI: 10.1051/0004-6361/201117961
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous molecules in the oxygen-rich circumstellar environment of binary post-AGB stars

Abstract: Context. The circumstellar environment of evolved stars is generally rich in molecular gas and dust. Typically, the entire environment is either oxygen-rich or carbon-rich, depending on the evolution of the central star. Aims. In this paper we discuss three evolved disc sources with evidence of atypical emission lines in their infrared spectra. The stars were taken from a larger sample of post-AGB binaries for which we have Spitzer infrared spectra, characterised by the presence of a stable oxygen-rich circumb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 72 publications
4
80
0
Order By: Relevance
“…In our own Milky Way, these C 60 infrared features were recently detected in five PNe, including Tc1, M1-12, M1-20, K3-54, and M1-60 (Cami et al 2010;García-Hernández et al 2010), a C-rich PPN (IRAS 01005+7910; Zhang & Kwok 2011), and two O-rich post-AGB stars (IRAS 06338+5333 and HD52961; Gielen et al 2011). In Figure 8, we show the IRS spectrum of M1-12 compared to M1-11.…”
Section: μM Emission Due To C 60 Fullerenesmentioning
confidence: 78%
See 1 more Smart Citation
“…In our own Milky Way, these C 60 infrared features were recently detected in five PNe, including Tc1, M1-12, M1-20, K3-54, and M1-60 (Cami et al 2010;García-Hernández et al 2010), a C-rich PPN (IRAS 01005+7910; Zhang & Kwok 2011), and two O-rich post-AGB stars (IRAS 06338+5333 and HD52961; Gielen et al 2011). In Figure 8, we show the IRS spectrum of M1-12 compared to M1-11.…”
Section: μM Emission Due To C 60 Fullerenesmentioning
confidence: 78%
“…Recent Spitzer/IRS studies show that fullerenes C 60 are detected in several young PNe, a proto-PN (PPN), and two post asymptotic giant branch (post-AGB) stars in the Milky Way (Cami et al 2010;García-Hernández et al 2010;Zhang & Kwok 2011;Gielen et al 2011) and also in a handful of young PNe in the Magellanic Clouds (García-Hernández et al 2011a;Bernard-Salas et al 2012). The detection cases are increasing, however, the excitation and formation mechanism is still unclear (e.g., Cami et al 2011;García-Hernández 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, HD 52961 is an interesting target for a similar study to the one presented here. The primary in this evolved binary also displays an extreme depletion pattern and the infrared spectrum indicates the presence of PAH molecules, fullerenes, and CO 2 (Gielen et al 2011b). However, silicate emission is also detected.…”
Section: Discussionmentioning
confidence: 92%
“…Long after the initial proposed identification of C + 60 in the ISM by Foing & Ehrenfreud (1994) taking advantage of the laboratory spectrum of Fulara et al (1993a), the presence of C 60 + has been recently confirmed in diffuse interstellar clouds and the presence of C 60 previously in various environments as described by Cami (2014) and Berné et al (2015b), among others: various types of carbon-rich planetary nebulae (Cami et al 2010;García-Hernández et al 2010, 2011aGielen et al 2011, Otsuka et al 2013); a single pre-planetary nebula (Zhang & Kwok 2011); various interstellar environments (Rubin et al 2011;Peeters et al 2012;Boersma et al 2012), including reflection nebulae such as NGC 7023 (Sellgren et al 2007(Sellgren et al , 2010Berné & Tielens 2012) and young stellar objects (Roberts et al 2012).…”
Section: Interstellar Abundancesmentioning
confidence: 97%